2021
DOI: 10.3847/1538-4357/ac1bb2
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Rays from Fast Black-hole Winds

Abstract: Massive black holes at the centers of galaxies can launch powerful wide-angle winds that, if sustained over time, can unbind the gas from the stellar bulges of galaxies. These winds may be responsible for the observed scaling relation between the masses of the central black holes and the velocity dispersion of stars in galactic bulges. Propagating through the galaxy, the wind should interact with the interstellar medium creating a strong shock, similar to those observed in supernovae explosions, which is able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 97 publications
3
39
0
Order By: Relevance
“…As not many blazars may live within the GZK horizon, this implies that along with the blazar jet one may invoke as production site for the neutrinos additional scenarios such as neutrino emission from AGN-driven winds and/or diskcorona models. The excess of neutrinos in the direction of the misaligned jetted galaxy NGC 1068 reported by the IceCube collaboration (Aartsen et al 2020) and the detection of hadronic γ rays from ultra fast outflows hosted in AGN (Ajello et al 2021) support this hypothesis.…”
Section: Pevatron Blazars Are Cosmic Rays Factoriesmentioning
confidence: 91%
“…As not many blazars may live within the GZK horizon, this implies that along with the blazar jet one may invoke as production site for the neutrinos additional scenarios such as neutrino emission from AGN-driven winds and/or diskcorona models. The excess of neutrinos in the direction of the misaligned jetted galaxy NGC 1068 reported by the IceCube collaboration (Aartsen et al 2020) and the detection of hadronic γ rays from ultra fast outflows hosted in AGN (Ajello et al 2021) support this hypothesis.…”
Section: Pevatron Blazars Are Cosmic Rays Factoriesmentioning
confidence: 91%
“…83,88]. This has been detected very recently in AGN with ultra-fast outflows (UFOs) through a stacking analysis by Fermi [10].…”
Section: Agn As High-energy and Multi-messenger Sourcesmentioning
confidence: 93%
“…In fact, blazars make up ∼ 60% of the Fermi sky and the vast majority of extragalactic γ-ray sources [48], while 92% of extragalactic objects above 1 TeV 7 are also blazars, studied mostly with Imaging Atmospheric Cherenkov Telescopes (IACTs) such as MAGIC 8 , H.E.S.S. 9 , and VERITAS 10 . IACTs, unlike Fermi, have a relatively small field of view and observe from the ground the particle showers produced by the impact of very high-energy (∼ 50 GeV -10 TeV) γ-ray photons on the top layers of the atmosphere, either through the Cherenkov light they generate, or via the direct detection of the charged particles in the shower.…”
Section: Agn As High-energy and Multi-messenger Sourcesmentioning
confidence: 99%
“…The above estimates serve as an indication that the emission from individual molecular outflows is likely below the sensitivity of Fermi-LAT, and therefore motivates the use of a stacking technique in order to detect emission from the overall population. The method employed is the same as that applied successfully in a number of previous studies (e.g., Fermi-LAT Collaboration et al 2018;Paliya et al 2019;Ajello et al 2020Ajello et al , 2021. For this procedure, we work under the assumption that the sample population can be characterized by average quantities such as flux, luminosity, or photon index.…”
Section: Stacking Analysismentioning
confidence: 99%
“…The efficiency of cosmic-ray acceleration in outflows is predicted to be comparable to or in excess of other acceleration sites such as supernova remnants (SNRs; Faucher-Giguère & Quataert 2012; Nims et al 2015). Recently, the detection of gamma rays from highly ionized, ultra-fast outflows (UFOs) using Fermi-LAT data has been reported (Ajello et al 2021), and it is possible that molecular outflows may also be observed in gamma rays (Lamastra et al 2016). In fact, several of the galaxies that are known to host powerful outflows are also gamma-ray emitters with significant detections by Fermi-LAT (Abdo et al 2010a;Lenain et al 2010;Ackermann et al 2012;Hayashida et al 2013;Tang et al 2014;Ajello et al 2020), as well as by other higher-energy gamma-ray telescopes (Acero et al 2009;VERITAS Collaboration et al 2009).…”
Section: Introductionmentioning
confidence: 99%